2019
DOI: 10.1016/j.nedt.2019.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Learning procedural skills with a virtual reality simulator: An acceptability study

Abstract: Background: Virtual Reality (VR) simulation has recently been developed and has improved surgical training. Most VR simulators focus on learning technical skills and few on procedural skills. Studies that evaluated VR simulators focused on feasibility, reliability or easiness of use, but few of them used a specific acceptability measurement tool. Objectives: The aim of the study was to assess acceptability and usability of a new VR simulator for procedural skill training among scrub nurses, based on the Unifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 16 publications
8
96
0
2
Order By: Relevance
“…It should be noted that the comparisons in this study were made with a fairly small sample size (but in line with previous similar studies, see An et al, 2018;Bracq et al, 2019;Liang et al, 2019). A larger sample size would increase the statistical power; for example, the inclusion of participants with a higher degree of SS may provide a better understanding on how discomfort during the VR simulation may affect task performance.…”
Section: Limitationssupporting
confidence: 61%
See 1 more Smart Citation
“…It should be noted that the comparisons in this study were made with a fairly small sample size (but in line with previous similar studies, see An et al, 2018;Bracq et al, 2019;Liang et al, 2019). A larger sample size would increase the statistical power; for example, the inclusion of participants with a higher degree of SS may provide a better understanding on how discomfort during the VR simulation may affect task performance.…”
Section: Limitationssupporting
confidence: 61%
“…All the participants self-reported to be right-handed with no intake of psychotropic drugs, history of psychiatric/psychological illness, photosensitivity, or epilepsy seizures. The sample size was chosen to be in line with the ones reported by recently published papers that have investigated the effect of VR on training ( An et al, 2018 ; Bracq et al, 2019 ; Liang et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…An overview of these studies, their methodologies, and their findings are reported in Table 1 . Two of the included studies were published in 2016 (Allen et al, 2016 ; Robert et al, 2016 ), three in 2017 (Cárdenas-Delgado et al, 2017 ; Munafo et al, 2017 ; Wilson and Kinsela, 2017 ), eight in 2018 (An et al, 2018 ; Juan et al, 2018 ; Khashe et al, 2018 ; Melo et al, 2018 ; Mousas et al, 2018 ; Rangelova and Marsden, 2018 ; Roettl and Terlutter, 2018 ; Scheibler and Rodrigues, 2018 ), eight in 2019 (Al Zayer et al, 2019 ; Bracq et al, 2019 ; Chang et al, 2019 ; Clifton and Palmisano, 2019 ; Liang et al, 2019 ; Moroz et al, 2019 ; Narciso et al, 2019 ; Shafer et al, 2019 ), and one in 2020 (Curry et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Narciso et al ( 2019 ) reported that males and females may be sensitive to different features of the simulated environment and experience discomfort (nausea) accordingly (females more for two-dimensional [2D] environments, while males for three-dimensional [3D] environments). Seven of the analyzed studies did not report differences in SS and discomfort during VR simulation between male and female participants (experiment 1 in Munafo et al, 2017 ; Wilson and Kinsela, 2017 ; Melo et al, 2018 ; Al Zayer et al, 2019 ; Bracq et al, 2019 ; Clifton and Palmisano, 2019 ). Figure 2 displays the studies that reported increased discomfort between males and females, divided by the type of utilized HMD equipment and categories of VR content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation